Pengaruh Customer Experience Management Terhadap Customer Loyalty - Deni Krisyanto; Ayu Ekasari (Universitas Kristen Indonesia Toraja, 2024)
This research aims to examine the factors that influence consumer loyalty among consumers in the banking industry. Therefore, the author develops a framework that illustrates that there is a positive relationship between the physical environment, visual environment, and interaction services on consumer loyalty to banks. An online survey was conducted with a sample of 220 respondents as bank users. The results show that there is a positive influence of physical interaction management, visual interaction management, service interaction management on customer loyalty. This survey is aimed at customers who are loyal to the bank and have made transactions at the bank for more than three months, both physical transactions and visual transactions in the banking sector.